2009
DOI: 10.1037/a0014936
|View full text |Cite
|
Sign up to set email alerts
|

Predicting longitudinal patterns of functional deficits in children with traumatic brain injury.

Abstract: Longitudinal patterns of functional deficits were investigated in 37 children with severe traumatic brain injuries (TBI), 40 children with moderate TBI, and 44 children with orthopedic injuries (OI). They were from 6 to 12 years of age when injured. Their neuropsychological, behavioral, adaptive, and academic functioning was assessed at 6 months, 12 months, and 3-5 years post injury. Functional deficits (<10th percentile for age) were identified within each outcome domain at each occasion. Children were classi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
85
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(95 citation statements)
references
References 62 publications
9
85
0
1
Order By: Relevance
“…The authors believed that this reflected significant and persistent neurocognitive impairments in a subset of children with severe TBI (Babikian & Asnarow, 2009). Such a variation within the severe group is supported by the results of Fay et al (2009) in their person-oriented study of functional deficits over time in individual children. There was a pronounced variation within the group of the severely injured, covering persons with four persistent deficits to persons with few deficits 4 years post-injury.…”
Section: Time Since Injurysupporting
confidence: 51%
See 2 more Smart Citations
“…The authors believed that this reflected significant and persistent neurocognitive impairments in a subset of children with severe TBI (Babikian & Asnarow, 2009). Such a variation within the severe group is supported by the results of Fay et al (2009) in their person-oriented study of functional deficits over time in individual children. There was a pronounced variation within the group of the severely injured, covering persons with four persistent deficits to persons with few deficits 4 years post-injury.…”
Section: Time Since Injurysupporting
confidence: 51%
“…Fay et al (2010) reported that children who prior to the injury had a lower cognitive ability had an increased number of symptoms reported after a mild TBI. Pre-injury behavioural functioning has been reported to be a predictor of post-injury behavioural functioning ( Taylor et al, 2002;Fay et al, 2009). The influence of the environment on children"s CRC is seen in a study by Yeates et al, (2004), where pre-injury familyrelated environmental factors characterised by a lower socioeconomic status, fewer family resources and poorer family-functioning moderated the longterm social outcome of a CTBI in a negative manner.…”
Section: Cognitive Reserve Capacitymentioning
confidence: 95%
See 1 more Smart Citation
“…Specifically, externalizing behavior problems have been reported to develop within 1 year following the injury for a large percentage of children with TBI and persist well beyond the post-acute recovery phase (i.e., 3 to 6 months post-injury) for up to 50% of children with severe TBI (Fay et al, 2009;.…”
Section: Behavioral Outcomes Following Early Childhood Tbimentioning
confidence: 99%
“…In recent years, however, the long-term impact of TBI in childhood has received increased research attention. Specifically, research studies have focused on increasing the understanding of developmental trajectories for school-aged children with TBI and developing appropriate interventions to ameliorate post-injury problems, such as cognitive and behavioral deficits (Fay et al, 2009;Taylor et al, 2001. Despite the increased research attention currently directed toward childhood TBI, the negative consequences of TBI have been studied less frequently in children younger than 5 years compared to children older than 5 years (Coleman, 2011).…”
Section: Traumatic Brain Injury In Children: a Significant Public Heamentioning
confidence: 99%